2023
DOI: 10.1186/s12889-023-16620-9
|View full text |Cite
|
Sign up to set email alerts
|

Health condition, income loss, food insecurity and other social inequities among migrants and refugees during the COVID-19 pandemic in Brazil

Heriederson Sávio Dias Moura,
Thaís Zamboni Berra,
Rander Junior Rosa
et al.

Abstract: Background Brazil is the destination of many international migrants and refugees and, given the circumstances of their entry into the country, many face difficulties due to the absence of targeted policies. Thus, the objective of this study was to survey the social impact of COVID-19 on international migrants and refugees regarding income loss, food insecurity and other social inequities, and to identify explanatory factors on these aspects. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
1
2
0
1
Order By: Relevance
“…Migrant women, in particular, fled a culture of exploitation and gender-based violence in their countries of origin (48). COVID-19 worsened the pre-existing conditions of the most vulnerable population groups, and exacerbated inequality and marginalization (21). Consistent with other studies, MIMs faced specific challenges brought about by the COVID-19 pandemic (49).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Migrant women, in particular, fled a culture of exploitation and gender-based violence in their countries of origin (48). COVID-19 worsened the pre-existing conditions of the most vulnerable population groups, and exacerbated inequality and marginalization (21). Consistent with other studies, MIMs faced specific challenges brought about by the COVID-19 pandemic (49).…”
Section: Discussionsupporting
confidence: 65%
“…This study has highlighted the fragile health systems in the countries of origin, poor health coverage and the shortage of beds for COVID-19 patients (52,53). The results have shown that many MIMs were working in informal sectors incompatible with the remote work encouraged by the confinement measures (21). The imposition of movement restrictions meant that the MIMs lost jobs and therefore income (54).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…O desemprego e queda dos salários decorrentes das novas adaptações causadas pelo isolamento são dois problemas que incentivam a população e seus respectivos governos a considerar medidas de transição para livre circulação 70% da população brasileira depende exclusivamente do SUS, tendo ações voltadas para a promoção, a prevenção e a assistência à saúde (Frenk & Moon, 2013). Durante a pandemia ocorreu uma sobrecarga destes serviços, aumentando o gasto público ao ponto de não haver medicamentos e equipamentos, além de faltar profissionais, tendo como única saída a realocação de recursos, ou seja, transferir do setor menos afetado para o mais afetado (Moura et al, 2023).…”
Section: Introductionunclassified